Feasibility in using mobile health application among chronic kidney disease patient on haemodialysis in Hospital Universiti Sains Malaysia - Johan, Nurul Aina Syahidah Che (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Mobile health can be a significant tool for improving population health, particularly for chronic disease patients. However, the health of the users may limit the full potential of mobile health application. The aim of this study was to assess feasibility in using mobile health application among chronic kidney disease in Hospital USM. A cross-sectional study was undertaken involving 100 participants using purposive sampling. The questionnaire using interview face to face was used for data collection from February 2021 until March 2021. Spearman’s correlation test was used to examine the relationship between level of ability in using smartphone and level of readiness in using mobile health application. The findings revealed that the majority 46% had good ability in using smartphone and 78% was ready to use mobile health application. There is significant, strongly, positive association between level of ability with level of readiness in using mobile health application (r=0.4, p<0.05). In conclusion, positive feedback from all respondents about mobile health application though that not all respondents able to use smartphone by themselves but they still want to use mobile health application for manage their health at home.